Mitotic chromosome condensation - Belmont, Andrew (Henry Stewart Talks, 2009)
Evolutionary and developmental comparisons, Stages of mitosis, Primary functions of mitosis, Lower levels of chromatin organization, Helical folding, Experimental foundation of textbook model, Are there specific DNA sequences at the base of chromatin loops?, Are there specific nonhistone proteins making up the chromosome scaffold?, Three independent experimental paths led to identification of condensin complex containing Sc2, SMC family of proteins, Condensation by condensins, Challenges to textbook model, progressive condensation during prophase, Alternative model: Radial loop, helical coil model, What we think we know, What we'd like to know, Alternative mechanism for chromosome condensation, How do we integrate structural studies of chromosome structure with chromosome biochemistry, We need a better understanding of chromosome structure